A dialogue about the South African “here and now” with the legacies of the early church fathers as interlocutors - Smith, TJ (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
This article explores what the missional possibilities could be when we explore the present discourse on the Early Church Fathers, with a view to understand our missional calling in the context of post-apartheid South Africa. Three dialogues explore issues of agency, inheritance and consumerism. These dialogues or interruptions open up new conversations that could lead to new imaginations.